IMMUNE THROMBOTIC THROMBOCYTOPENIC PURPURA: PATHOPHYSIOLOGY, DIAGNOSIS AND OPEN ISSUES. - Silvia Maria Trisolini; Alessandro Laganà; Saveria Capria (Mediterranean Journal of Hematology and Infectious Diseases)
Immune thrombotic thrombocytopenic purpura (iTTP) is a life-threatening thrombotic microangiopathy characterized by microangiopathic hemolytic anemia, thrombocytopenia, and ischemic end organ injury due to microvascular platelet-rich thrombi. iTTP pathophysiology is based on a severe ADAMTS13 deficiency, the specific von Willebrand factor (vWF)-cleaving protease, due to anti-ADAMTS13 autoantibodies. Early diagnosis and treatment reduce the mortality. Front-line therapy includes daily plasma exchange (PEX) with fresh frozen plasma replacement and immunosuppression with corticosteroids. Caplacizumab is recently added to the front-line therapy. Caplacizumab is a nanobody that binds to the A1 domain of vWF, blocking the interaction of ultra-large vWF multimers with the platelet, and thereby preventing the formation of platelet-rich thrombi. Caplacizumab reduces mortality due to ischemic events, refractoriness and exacerbations after PEX discontinuation. Until now, the criteria for response to treatment mainly took into account the normalization of platelet count and discontinuation of PEX, now with the use of caplacizumab, leading to rapid normalization of platelet count, it has been necessary to redefine the response criteria, taking into account also the underlying autoimmune disease. Monitoring of ADAMTS13 activity is important to identify cases with low value of activity (<10IU/L), requiring the optimization of immunosuppressive therapy with addition of rituximab. Rituximab is effective in patients with refractory disease or relapsing disease, currently the use of rituximab has expanded, both in front line treatment, and during follow-up as pre-emptive approach. Some patients do not achieve an ADAMTS13 remission following the acute phase despite steroids and rituximab treatment, requiring an individualized immunosuppressive approach to prevent clinical relapse. In iTTP, there is an increased risk of venous thrombotic events (VTEs) as well as arterial thrombotic events and most occur after platelet normalization. Until now, there is no consensus on the use of pharmacological thromboprophylaxis in patients on caplacizumab, because the drug is known to increase bleeding-risk.